The aetiology of Paget's disease of bone: with special reference to its relation to neoplasia - Wilkie, Elsie Bowman (The University of Edinburgh, 1911)
1. The main histological features of= Paget's disease are, a progressive reduction of certain of the bones, together with a characteristic replacement of the ordinary by delicate fibrous or fibrillar marrow.

Associated with this there is a striking disappeatance of the lymphoid and myeloblastic elements in that rmarrow.

2. This presents no indication of being an inflammatory process, or an after result of the same but hGs all the marks of being an atrophic process, coupled with a certain grade of kataplasia or modified conditions of the function of the osteoblastic elements.

In a certain percentage of cases of Paget's disease, this process is complicated by a further modification of the osteoblastic elements in different regions of the bone, characterised by a more active proliferation of the osteoblasts .n these regions and replacement of the simple fibrous by a fibro -hyaline matrix.

3. Where this condition shows itself, the overgrowth is diffuse, involving progressively the osteoblasts over larger and larger areas, leading thus to an osteold overgrowth.

4. Careful study of the features of this over - growth indicate that here we deal with a blastomatoid condition and not with the development of true localised tumours of the ordinary type, or blastomas proper.

5. Such blastomatoid outgrowths may give origin in certain portions of the same, to definite malignant sarcomatous development. Whereas the simple blastomatoid growth is purely local and respects the original boundaries of the tissue, having no tendency to infiltrate, regions of the sarcomatous growth do not respect these boundaries and infiltrate the surrounding tissues.

6. A survey of neoplastic states in general shows that this blastornatoid growth, as distinct from unicentric (or pluricentric) sharply defined centrifugal tumours of the ordinary type - is more frequent than is generally recognised.

Examples are given of such blastomatoid conditions involving fatty tissues, neural tissue, neuroglia, lymphoid tissue. It is shown that members of this group have many features in common, e.g., hereditary tendency, tending to multiplicity of growths, merging into the surrounding tissue, the presence of txophic changes elsewhere, and tendency to late sarcomatous change.

Next the subject of the Leukaemi s and peeudo leukaemia and chloroma is touched upon and extracts 'given from eminent authorities showing the growing tendency to recognise their probable relationship on the one hand to neoplasia and on the other hand to diseases of bone marrow.

7. In connection with bone. -- Multiple exostoses are characteristically diffuse, localised overgrowths of perfectly formed bone, not sharply separated off from the surrounding bony matrix, and these must be regarded as blastomatoid types.

a. But in addition to such primary blastolmatoid, and the secondary blastomatoid states, as already noted, occurring in Paget's disease, the myeloblastic eleI!1ents of the bone may exhibit a similar diffuse growth.

The so- called layeloma multiplex can only be regarded as a myclomatosis or blastomatoid overgrowth [ M I S S I N G - P A G E ] ...

These considerations, coupled rrith the fact that metabolism experiments in Paget's disease, osteomalacia and the allies' conditions, indicate grave metabolic disturbances, suggest that in future more exact studies be made upon the condition of the ductless glands in Paget's disease and the associated conditions. The data at present in our possession are too inadequate to permit us to lay down with any precision, that these tumours are primarily due to some disturbed equilibrium between the various internal st cretins. But studying and analysing the very numerous hypotheses that have been advanced in connection with Paget's disease, it may be said that the hypothesis of some constitutional disturbance of metabolism has more in its favour and less, against it than any of its fellows .

11. A tentative classification is afforded of what may be termed the "trophic bone disturbances" and the thesis closes with an analysis of cases upon which the paper is based, together with a table recording all cases of Paget's disease in wrhich the diagnosis has been well established by autopsy, X -rays or microscopic examination.

A full classified bibliography of recorded cases of Paget's disease of Bone, and other works consulted is also appended.